Crescimento e produtividade do meloeiro sob diferentes lâminas de água e doses de Nitrogênio e Potássio - Andrade, Maria Edileuza Leite de (2006)
In the northeastern semi-arid the potentialities for the irrigated cultivation of fruits, by the peculiarities of constant luminosity and temperature almost the whole year around. The cultivation of the melon tree has expressive representativity in the guide lines of the exportation of fruits. For that matter, this study had as objective to evaluate the growth of the melon Pele de Sapo under different levels of water and doses of Nitrogen and Potassium. The research was carried out in the city of Mossoró-RN, in 2004, and consisted of the simultaneous installation of three experiments, which were irrigated with different levels (L1: 281, L2: 349 and L3: 423 mm). Each experiment was established in randomized blocks delineating in the factorial scheme 3 x 3 + 2, being three proportions of N (N0: 0 kg.ha-1, N1:91 kg.ha-1 and N3: 184 kg.ha-1), three doses of K (K0: 0 kg.ha-1, K1: 174 kg.ha-1 and K3: 346kg.ha-1), more additional doses (N0K2 and N2K2) with three repetitions. The leaf area was evaluated, number of leaves, leaf dry matter of the upper part, absolute growth rate of the upper part, rate of relative growth of the upper part, liquid absorption rate of the upper part and commercial production. All the evaluated characteristics of growth and productivity were significantly influenced by the irrigation levels and doses of Nitrogen. The doses of Potassium did not influence any of the characteristics. The growth was slow in the beginning of the sowing circle, getting intense up to around 38 days after the sowing process, getting to its maximum point between 64 and 65 days. Concerning the rates of growth, tendencies of ascention and fall along the sowing circle were evidenced, as to the level of water as to the doses of Nitrogen and Potassium. Higher amounts of the correlation coefficient were obtained in the beginning, 28 after sowing, and at the end, after 70 days. The marketable and total average production of the melon Pele de Sapo was obtained as the quantity of water for the plants was increased, reaching average amounts in levels of 26,50 Mg ha-1 and 32,93 Mg ha-1, respectively, and the doses of N of 25,50 and 31,64 kg ha-1 and doses of K of 26,67 and 35,03 kg ha-1, respectively